A Taqriz for a Nineteenth Century Indonesian Manuscript - Kaptein, Nico J.G. (Center for Research and Development of Religious Literature and Heritage, 2015)
In medieval Arabic literature a taqrÂ³Â§ is a written endorsement of a certain text, which a prestigious scholar provides at the request of another scholar to support the latterâs new writing. In this sense it can be compared to the contemporary âblurbâ, to advertise a new book. The taqrÂ³Â§ is important because it connects and offers insights into active networks of like-minded scholars. Unfortunately this topic is still insufficiently studied and the present paper aims to make a contribution to this subject. The research examines an original taqrÂ³Â§ from the nineteenth century which a scholar in Batavia obtained from his former teacher in Mecca. The paper shows that the taqrÂ³Â§ is also in existence in more modern times and even beyond the Arab world.